EFFECT OF TOLTRAZURIL 2.5% DURING THE PREPATENT PERIOD OF CANINE SARCOCYSTIOSIS - Vilca M., Julio (2007)
The aim of the study was to determine the effect of toltrazuril (2.5%) in a single dose for the treatment of canine sarcocystiosis. Twenty-four crossbred puppies, both sexes, 2.5 months of age, were used. All puppies were dewormed prior to the study and fed throughout the study with a diet free of raw meat. Animals were experimentally infected with nearly 95,000 cysts of S. lamacanis, contained in 100 g of alpaca heart, and distributed in a control (untreated) group of 4 puppies and 4 groups of 5 puppies each which were treated with toltrazuril (2.5%) with a single dose of 10 or 20 mg/kg body weight on day 5 or 7 post-infection. Fecal samples were daily collected during 11 days and starting on day 10 post-infection. Feces was analyzed by the flotation method with the Sheather solution to determine the presence of sporocysts of Sarcocystis sp. and positive samples were analyzed by the modified Stoll method to determine the number of sporocysts per gram of feces. The toltrazuril did not control the infection of S. lamacanis in none of the treated groups.